SIR-A views our environment An Experiment in the Batu Angkal Area, West Kalimantan, Indonesia - Sutanto Sutanto; Zuharnen Zuharnen (Indonesian Journal of Geography, 1986)
Cloud cover is a serious problem for remote sensing in Indonesia. Some areas, around 10% to 20% of the land territory, are almost never cloud-free. The only system of remote sensing capable of overcoming cloud cover problem is that applying microwave energy. This article deals with a radar system being operated by the Columbia shuttle imaging radar A in 1981 in the Batu Angkal area, West Kalimantan, Indonesia. The choice of the study area is due to the availability of collateral material such as topographic map. land use map, and false color photographs.The study is aimed at learning the interpretability of SIR-A image of 1:500,000 which is blown up to 1:250,000 for the study of the.environment of this area. The method used in the identification of environment is applying the physical characteristics of objects (tone, texture, shape, size, direction in relation to the illumination, surface roughness, and dielectric constant) to trace it.The discernable elements of the environment of the study area are listed sequentially based on the ease of identqicaiton: rivers and dissected hills, unpaind forest and lowland forest, wetfields, and road and settlement.Factors affecting the ease of identification are. mainly tonal contrast, shape, size, surface roughness, direction in relation to the illumination, and dielectric constant. Due to the future availability of SIR-B image of Kalimantan, further study is recommended.